Would Illness Representations of COVID-19 and COVID-19 Fears During Clinic Visits Promote or Reduce Behavioral Intention to Seek Medical Consultations for Flu Symptoms? A Random Telephone Survey in Hong Kong, China - Luo, Sitong; She, Rui; Lau, Mason M. C.; Lau, Joseph T. F. (Frontiers in Public Health, 2022)
Background The study investigated the level of behavioral intention to consult doctors for flu symptoms (BICDFS) during the Coronavirus Disease 2019 (COVID-19) pandemic and examined its associations with illness representations of COVID-19 and fear of COVID-19 during clinic visits in a general Chinese adult population. Methods A random telephone survey was conducted among 300 residents in Hong Kong, China in April 2020 when the second wave of COVID-19 was just ended in the region. The participants were asked about their intention to consult doctors if they had mild or severe flu symptoms in the next week (from 1 = definitely no to 5 = definitely yes). Illness representations of COVID-19 were measured by the Chinese version of the Brief Illness Perception Questionnaire (BIPQ). The fear of COVID-19 during clinic visits were assessed by two single items. Linear regression adjusted for background variables and hierarchical strategies were employed. Results Of the participants, 52.3 and 92.0% showed an intention to consult doctors for mild and severe flu symptoms, respectively. Adjusted for background factors, COVID-19-related cognitive representations (consequences: standardized b = 0.15, p = 0.010; understanding: standardized b = 0.21, p = 0.001) and emotional representations (concern: standardized b = 0.17, p = 0.001; negative emotions: standardized b = 0.19, p = 0.001) were positively associated with BICDFS. In the hierarchical model, independent significant factors of BICDFS included understanding (standardized b = 0.16, p = 0.013) and negative emotions (standardized b = 0.17, p = 0.008). The fear-related variables showed non-significant associations with the BICDFS. Conclusions Promotion of care-seeking behaviors for flu symptoms during the COVID-19 pandemic should consider improving people's understanding of COVID-19 and providing advice on related coping strategies for emotional responses to COVID-19.